A study of the prognostic usefulness of blood leukocyte changes in canine parvoviral enteritis - Christopher, M.M. (University of Pretoria, 2013)
Dissertation (Master in Veterinary Medicine(Clinical Laboratory Diagnostics))--University of Pretoria, 2006.